Challenges for the development of a universal vaccine against leptospirosis revealed by the evaluation of 22 vaccine candidates - Maia, Mara A. C.; Bettin, Everton B.; Barbosa, Liana N.; de Oliveira, Natasha R.; Bunde, Tiffany T.; Pedra, Ana Carolina K.; Rosa, Guilherme A.; da Rosa, Elias E. B.; Seixas Neto, Amilton C. P.; Grassmann, André A.; McFadden, Johnjoe; Dellagostin, Odir A.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Leptospirosis is a neglected disease of man and animals that affects nearly half a million people annually and causes considerable economic losses. Current human vaccines are inactivated whole-cell preparations (bacterins) of Leptospira spp. that provide strong homologous protection yet fail to induce a cross-protective immune response. Yearly boosters are required, and serious side-effects are frequently reported so the vaccine is licensed for use in humans in only a handful of countries. Novel universal vaccines require identification of conserved surface-exposed epitopes of leptospiral antigens. Outer membrane β-barrel proteins (βb-OMPs) meet these requirements and have been successfully used as vaccines for other diseases. We report the evaluation of 22 constructs containing protein fragments from 33 leptospiral βb-OMPs, previously identified by reverse and structural vaccinology and cell-surface immunoprecipitation. Three-dimensional structures for each leptospiral βb-OMP were predicted by I-TASSER. The surface-exposed epitopes were predicted using NetMHCII 2.2 and BepiPred 2.0. Recombinant constructs containing regions from one or more βb-OMPs were cloned and expressed in Escherichia coli. IMAC-purified recombinant proteins were adsorbed to an aluminium hydroxide adjuvant to produce the vaccine formulations. Hamsters (4-6 weeks old) were vaccinated with 2 doses containing 50 – 125 μg of recombinant protein, with a 14-day interval between doses. Immunoprotection was evaluated in the hamster model of leptospirosis against a homologous challenge (10 – 20× ED50) with L. interrogans serogroup Icterohaemorrhagiae serovar Copenhageni strain Fiocruz L1-130. Of the vaccine formulations, 20/22 were immunogenic and induced significant humoral immune responses (IgG) prior to challenge. Four constructs induced significant protection (100%, P < 0.001) and sterilizing immunity in two independent experiments, however, this was not reproducible in subsequent evaluations (0 – 33.3% protection, P > 0.05). The lack of reproducibility seen in these challenge experiments and in other reports in the literature, together with the lack of immune correlates and commercially available reagents to characterize the immune response, suggest that the hamster may not be the ideal model for evaluation of leptospirosis vaccines and highlight the need for evaluation of alternative models, such as the mouse.